Who Is There For Me? Evaluating the Social Support Received by Adolescent Girls Transitioning From Institutional Care in Zimbabwe. Issue 1 (1st January 2017) - Berejena Mhongera, Pamhidzayi; Lombard, Antoinette
Abstract : Adolescent girls draw resources from different stakeholders to meet their livelihood needs during and after institutional care. Thus, an understanding of the nature of social support being provided is important in addressing poverty in the institutional context. Using the DFID sustainable livelihood approach, this qualitative study evaluated the social capital being accessed by adolescent girls transitioning from two institutions in Harare, Zimbabwe. Institution A is state-owned whereas B is run by a non-governmental organisation. Semi-structured interviews were conducted with thirty-two adolescent girls (sixteen in care and sixteen care leavers) and two focus group discussions were held with eight girls in each participating institution. Results from the study suggest that due to limited capacity, lower levels of engagement by different transition stakeholders and a fragmented service delivery system, adolescent girls lack adequate social support during and after institutional care, resulting in poverty. To promote the achievement of sustainable livelihoods, the authors recommend the development of a service delivery model that provides a continuum of support to adolescent girls in the institutional context as a distinct social group and increased investments in transition research and programming.